SEXUALLY TRANSMITTED INFECTION: THE SYMPTOMATIC PRESENTATION AMONGST RURAL COMMUNITY OF LUCKNOW DISTRICT, UTTAR PRADESH - Patel, S P; Mohan, Uday; Srivastava, V K (Indian Journal of Community Health, 2012)
Background: India has a sudden rise in the incidence of STIs especially in the rural areas where it seemed hyper endemic. The reason is the inadequate health facilities for diagnosis and treatment of this infection. Objective: To appraise STIs based on syndromic approach corresponding socio-demographic characteristics in the rural community. Materials and Methods: The baseline study of adults 15 to 49 years of both sexes were enrolled through systematic random method for interviewing the STIs symptoms corresponding biosocial characteristic. Results: Out of the total 10.5% were diagnosed on the basis of symptoms (syndromic approach) of STIs where the commonest symptom was pus discharge from genital organs (71.7%). The prevalence rate in female population was found to be higher (14.2%) compared to prevalence in male (7.1%). In age composition the highest (15.3%) prevalence of STIs was observed in the age group of 30-34 year adults. The prevalence of STIs was quite low (6.9%) in adults educated up to high school. The occurrence of STIs in the study population was found to be steady increasing with lowering social class and maximum prevalence rate of STIs in the social class V was 13.6%. Conclusions: The 30-34 years age group of adults is sexually active and migrating in nature, these adults need counseling about use of condom. The lower social class adults are generally not taking proper treatment due to ignorance and poverty. Time to time a camp approach availably in rural area are good solution of high prevalence of these infections in villages.